Typography between shape and meaning (Damascus University Journal for engineering sciences, 2021)
The development of the design idea of printing character types require firm, variable knowledge of the components of the character form, space, and visual form. The more visual experience, the increased likelihood of building characters and forms within the a new vocabulary in a new visual sight, and this is what this research is the analysis of character patterns which the word design has been associated with the giving meaning and a pictures tic idea for that meaning where the typography world has invaded a wide visual and unlimited area that varies between surrounding form and diverse raw materials and functional value of characters.Where modern designer benefited from modern digital technologies to make this invented alphabets used in many programs to become a writing language through a digital mediator carrying numerous visual forms, easy to accomplish in a digital program, and, also, easy to write and circulate to find new alphabet involving meaning and help the visual message reach the recipient.